Аналіз матеріалів кримінальних впроваджень щодо незаконних рубок в лісах України - Лакида, Петро Іванович; Lakyda, Petro; Ситник, Світлана Анатоліївна; Sytnyk, Svitlana; Ловинська, Вікторія Миколаївна; Lovynska, Viktoriia; Голобородько, Кирило Костянтинович; Holoborodko, Kyrylo (My University, 2024)
Метою політики заборони експорту, широко відомої як «Обмеження експорту лісопродукції», у багатьох випадках є як економічні, так і екологічні цілі. Екологічні злочинці часто причетні до актів корупції, ухилення від сплати податків, іншими пов’язаними злочинами. Інтерпол підтримує країни-членів у зміцненні їхнього правоохоронного потенціалу в галузі лісового господарства та налагодженні міжнародного співробітництва між національними відомствами, аналізуючи всі види інформації, які сприяють або супроводжують незаконну лісо The purpose of export bans, commonly known as ‘Timber Export Restrictions’, in many cases has both economic and environmental objectives. Environmental criminals are often involved in acts of corruption, money laundering, other related crimes. INTERPOL supports its member countries in strengthening their forestry law enforcement capacity and establishing international cooperation between national agencies. In this way INTERPOL analysing all types of information that facilitate or accompany illegal forestry activities. The research method used to analyse criminal implementations was the process of evaluating data based on criminal intelligence analysis (criminal intelligence analysis – CIA). This method supports the decision-making process of investigators, managers, supervisors and other law enforcement agencies to use their limited resources more efficiently and effectively and to ensure an analytics-based policing approach. The article presents the results of the analysis of the materials of criminal investigations into illegal logging carried out in the forests of Ukraine. The analytical materials of criminal investigations will become the basis for the development of preventive measures that can discourage illegal logging. Also, in the same time the obtained analytical materials of criminal investigations will influence the creation of new and improvement of existing legal acts regulating liability for illegal logging. An analysis of criminal investigations in Ukrainian forests has led to the conclusion that most of the time illegal logging is carried out in natural areas in the such zone as the Ukrainian Carpathians and Polissia (47.4%). The main amount of illegal logging was carried out in forest stands (44.8%) and forests with protected status (28.9%). The main forest species targeted for felling are pine (41.7%), acacia (22.7%) and oak (21.1%). The organisers of the crimes are mainly individual entrepreneurs who has own timber processing enterprises and storage facilities (65.2%). Then the material damage caused by illegal logging is mostly not compensated (75.8%). This article offers recommended approaches to implementing the main areas of combating illegal logging in our country. The analytical materials can become the basis for the development of preventive measures to reduce quantities of illegal logging in the forests of Ukraine.
Analysis of criminal proceeding of illegal logging in the forests of Ukraine
Keywords: незаконні рубки; illegal logging; кримінальні впровадження; criminal enforcement; кримінальний кодекс України; Criminal Code of Ukraine